President University Students’ Employability Skills: The Influence of Gender, Academic Achievement, Area of Specialization, and Perceived Value of Internship Among Accounting Students - Cahyono, Petra Greatlynieda; Yanto, Ery (CV. Green Publisher Indonesia, 2025)
This study explores how gender, academic achievement, area of specialization, and perceived value of internship influence the employability skills of accounting students. The primary issue examined is the variation in employability skills and how these factors contribute to students’ job readiness. Motivated by the need to align educational outcomes with job market demands, this research aims to provide insights that can improve internship programs and better prepare students from professional careers. A quantitative approach was employed, collecting data from 107 final-year and alumni of accounting students at President University. The analysis revealed significant relationships between the variables and employability skills, with gender, academic achievement, area of specialization, and perceived value of internship all showing a notable impact. These findings align with existing theories on employability and provide evidence that internships are a key factor in skill development. However, limitations such as the focus on a single institution and the use of self-reported data suggest the need for broader research to generalize findings.